Using household flexibility as a part of demand-side management programs - Bilbiloska, Katerina (JET on-line, 2023)
This paper presents how customer flexibility can be used in the framework of a Demand Side Management (DSM) program. It focuses on household consumers, and aims to show how slight behavioural changes can lead to optimised use of household appliances and consequently, reduced energy costs. The paper presents a solution that would enable household customers to practice their flexibility. The solution is based on linear optimisation technique (LP) which is used to redistribute the use of domestic appliances throughout the day. The results show that implementation of the proposed solution can lead to reduction of hourly electricity use and reduce the overall electricity costs of the household. The optimised use of appliances reduces the household peak load more than 40% compared to the baseline scenario for all analysed cases. The optimisation implemented on specific households allows for reducing energy costs on average by 30%.
Keywords: demand side management; linear optimisation; linearna optimizacija; upravljanje povpraševanja